The soft skin = La peau douce - Delerue, Georges 1925-1992 (<<The>> Criterion Collection, 2015)
"Francçois Truffaut followed up the international phenomenon Jules and Jim with this tense tale of infidelity. The unassuming Jean Desailly is perfectly cast as a celebrated literary scholar, seemingly happily married, who embarks on an affair with a gorgeous stewardess, played by Francçoise Dorléac, who is captivated by his charm and reputation. As their romance gets serious, the film grows anxious, leading to a wallop of a conclusion. Truffaut made "The soft skin" at a time when he was immersing himself in the work of Alfred Hitchcock, and that master's influence can be felt throughout this complex, insightful, and underseen French New Wave treasure." [Cover]
Aspect ratio 1.66:1. - New high-definition digital restoration
Orig.: Frankreich 1964
Enth. audio commentary by screenwriter Jean-Louis Richard and François Truffaut scholar Serge Toubiana ; new video essay by filmmaker and critic Kent Jones ; "Monsieur Truffaut meets Mr. Hitchcock", a 1999 documentary by film historian Robert Fischer ; interview with Truffaut from 1965 about the film ; new english subtitle translation ; an essay by critic Molly Haskell
Keywords: Film